Light-mediated iodoperfluoroalkylation of alkenes/alkynes catalyzed by chloride ions: role of halogen bonding. Issue 54 (18th June 2018) - Beniazza, Redouane; Remisse, Lionel; Jardel, Damien; Lastécouères, Dominique; Vincent, Jean-Marc
Abstract : A catalytic amount of chloride ions greatly facilitates the UVA-mediated iodoperfluoroalkylation of alkenes and alkynes. Abstract : An innovative procedure for the iodoperfluoroalkylation of alkenes/alkynes is described. These reactions, including iodotrifluoromethylations of alkenes, proceed very efficiently under low intensity UVA irradiation in deoxygenated methanol solutions containing catalytic amounts of NaCl or Bu4 NCl. Preliminary mechanistic studies indicate that the light-promoted homolytic cleavage of the Rf –I bond that initiates the reaction is facilitated by the halogen bonding interaction between Rf I and chloride ions.